Evidence for action on improving the maternal and newborn health workforce: The basis for quality care. Issue 1 (4th December 2015) - Campbell, Jim; Sochas, Laura; Cometto, Giorgio; Matthews, Zoë
Abstract: Ambitious new goals to end preventable maternal and newborn deaths will not only require increased coverage but also improved quality of care. Unfortunately, current levels of quality in the delivery of maternal and newborn care are low in high‐burden countries, for reasons that are intimately linked with inadequate planning and management of the maternal and newborn health workforce. The Global Strategy on Human Resources for Health is a key opportunity to strengthen global and country‐level accountability frameworks for the health workforce and its capacity to deliver quality care. In order to succeed, maternal and newborn health specialists must embrace this strategy and its linkages with the new Global Strategy for Women's, Children's, and Adolescents' Health; action is needed across high‐ and low‐income countries; and any accountability framework must be underpinned by ambitious, measurable indicators and strengthened data collection on human resources for health.